ANALISIS PERAN MEGA, MACRO, DAN MICRO INFLUENCER DALAM PROMOSI PRODUK KECANTIKAN (STUDI PADA KONTEN INFLUENCER DI TIKTOK) - Marchella Sinolungan; Suryanto; Arianis Chan (JURNAL LENTERA BISNIS, 2025)
This research discusses the role of mega, macro, and micro influencers in promoting beauty products through the TikTok platform using the AISAS (Attention, Interest, Search, Action, and Share) approach. The purpose of this study is to analyze the role of influencers in attracting attention, building interest, encouraging information search, triggering purchases, and encouraging audiences to share promotional content. This research uses a descriptive qualitative method with a literature study approach and content analysis from TikTok social media. The results show that each level of influencer has a significant role in increasing consumer buying interest. Micro-influencers can reach specific audiences with authentic content, macro-influencers are trusted to provide in-depth reviews that are educative, while mega-influencers help increase brand awareness with a wider audience reach. This promotional strategy is proven to increase engagement, build trust, and impact sales of beauty products